Multiple surgical interventions improve survival in locally recurrent retroperitoneal sarcoma: a retrospective cohort analysis - Guojun Yan; Xinbao Li; Kai Zhang; Chao Gao; Lijun Yan; Xinjing Zhang; Songlin An; Yanbin Zhang (Frontiers in Oncology)
BackgroundLocally recurrent retroperitoneal sarcoma (RPS) poses substantial clinical challenges, especially in patients experiencing multiple recurrences. This study aims to evaluate the survival benefits conferred by repeated surgical resections in the management of recurrent RPS.MethodsA retrospective cohort study was conducted involving 56 patients who underwent repeated surgical resections for locally recurrent RPS at our institution between June 2016 and September 2023. Demographic, clinical, and histopathological variables- including age, sex, tumor differentiation, FNCLCC grade, prior radiotherapy and chemotherapy, surgical margin status, and postoperative complications -were collected and analyzed. Survival outcomes were assessed using Kaplan-Meier estimates and Cox proportional hazards models.ResultsThe median age of the cohort was 53 years (range: 28–72), with a male-to-female ratio of 30:26. Compared to a single resection, median overall survival (OS) improved with successive surgeries: 79.3 months for two surgeries, 158.0 months for three, and 181.7 months for four. However, OS declined to 121.9 months following five resections. Tumor differentiation and FNCLCC grade were significantly associated with survival outcomes. Multivariate analysis identified age, pathological subtype, tumor grade, and number of surgeries as independent prognostic factors. Although severe adverse events (SAEs) were recorded, no 30-day postoperative mortality occurred.ConclusionsRepeated surgical resection appears to confer substantial survival benefits in patients with locally recurrent RPS, underscoring the clinical value of surgical management in selected cases. These findings highlight the importance of individualized surgical strategies, while emphasizing the need for further investigation to optimize treatment paradigms.